1996
DOI: 10.4269/ajtmh.1996.54.197
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Artesunate Plus Tetracycline Versus Standard Treatment (Quinine Plus Tetracycline) for Uncomplicated Plasmodium falciparum Malaria in Brazil

Abstract: A triple 'blind randomized controlled trial was undertaken in a Brazilian Amazon region (Cuiabâ-MT), tn compare the effect;veness and side effects of oral artcsunate (7 days, total dose = 0.75 g) plus tetraeycline (7 days, total dose = 10.5 g) [AT) and oral quinine (3 days, total dose = 6 g) plus te(racydine (7 days, total dose = 10.5 g) [QT). Eligible patients had uncomph'c'ated P. falciparum malaria; age ~ 14 years; no previous malaria treatment related to ,the present attack; and, if women, indil,ation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 10 publications
1
14
0
1
Order By: Relevance
“…Between 2001 and 2007, uncomplicated falciparum malaria in Brazil was treated with quinine plus doxycycline (formerly tetracycline) for 7 days or a single MQ dose (15 mg/kg). 3 Clinical surveillance in the late 1990s revealed cure rates of 98.9% for MQ 4 and between 77.3% and 100% for quinine plus tetracycline 5,6 in northern Mato Grosso, central Brazil, despite emerging evidence for quinine 7 and MQ 8 resistance in vitro. The main P. falciparum transmission hotspot in the Amazon basin of Brazil is Juruá Valley, close to the border with Peru.…”
Section: Introductionmentioning
confidence: 99%
“…Between 2001 and 2007, uncomplicated falciparum malaria in Brazil was treated with quinine plus doxycycline (formerly tetracycline) for 7 days or a single MQ dose (15 mg/kg). 3 Clinical surveillance in the late 1990s revealed cure rates of 98.9% for MQ 4 and between 77.3% and 100% for quinine plus tetracycline 5,6 in northern Mato Grosso, central Brazil, despite emerging evidence for quinine 7 and MQ 8 resistance in vitro. The main P. falciparum transmission hotspot in the Amazon basin of Brazil is Juruá Valley, close to the border with Peru.…”
Section: Introductionmentioning
confidence: 99%
“…It is not clear whether these strains are associated with clinical failures. One strategy that health officials can pursue to reduce the prevalence of malaria is to combine QN with other antimalarial drugs such as tetracycline (8,18) or clindamycin (16).…”
mentioning
confidence: 99%
“…The derivative with the widest potential application is artesunate (ARTS), a water-soluble prodrug that can be administered parenterally as well as by mouth and per rectum. A number of studies have demonstrated the efficacy of ARTS in uncomplicated (17,19,24,26,27,28), severe (20,21), and multidrugresistant (11,25,34) falciparum malaria. Since ARTS clears parasites more rapidly than quinine and may improve survival (1,16,22,24,38), intravenous (i.v.)…”
mentioning
confidence: 99%